Assessing the Competencies of the Philippine Coast Guard’s Investigation and Detection Management Service: Reference to a Specialized Training Curriculum - Carlos, Carlos Victor (JPAIR Multidisciplinary Research, 2026)
The Philippine Coast Guard (PCG), as the country’s frontline in enforcing maritime laws, requires strong investigative capabilities to combat crimes such as smuggling, piracy, and illegal fishing across its extensive archipelago. This study was designed to evaluate the investigation and detection skills of the PCG’s Investigation and Detection Management Service (CGIDMS) and develop a specialized training curriculum. Using a mixed-method approach, the research involved interviews with senior officers and a scenario-based exam for 114 CGIDMS personnel. The assessment identified core competencies, measured existing skills, and analyzed the gaps between them. The best practices from international and local law enforcement agencies were also examined through document review. The findings revealed that CGIDMS personnel possess moderate competency, with an average score of 38.69 out of 60. While they demonstrated proficiency in briefings, legal compliance, and scene security, significant gaps were identified in intelligence gathering, forensic procedures, DNA interpretation, and evidence documentation and articulation. Triangulated data confirmed persistent needs for better legal preparedness and inter-agency coordination. Based on these results and analysis of best practices, the study proposed an Integrated Competency-Based Training Program. This modular, simulation-driven program focuses on strengthening legal compliance, forensic accuracy, and operational coordination. The research highlights the urgent need for systematic training reform to enhance the PCG’s investigative effectiveness and align it with international standards.